Processes and contexts influencing health inequalities among women who are mothers. Issue 10 (10th June 2019) - Trujillo-Alemán, Sara; Perez, Gloria; Reynolds, Jillian; Rueda, Silvia; Borrell, Carme
Abstract : This paper presents a conceptual framework that aims to conceptualise the different processes and contexts influencing health inequalities among women who are mothers. On the one hand, four processes are shown: (1) social stratification; (2) route into motherhood; (3) exposure and vulnerability to risk factors; and (4) generation of health inequalities. On the other hand, the role of the socioeconomic and political context, the labour market context, and the social, community and family context, as well as their inter-relationships, are presented. In addition, different family policy models, social values and cultural imperatives are considered.